Gingival Crevicular Fluid as Biomarker’s Source for Alzheimer’s Disease - Sansores-España, Luis Daniel; Morales, Francisca; Arriola-Pacheco, Fabio; Astorga, Jessica; Paula-Lima, Andrea; Carrillo-Ávila, Arelly; Melgar-Rodríguez, Samanta; Martínez-Aguilar, Víctor; Díaz-Zúñiga, Jaime (Odovtos - International Journal of Dental Sciences, 2021)
Periodontitis is a low-grade inflammatory disease caused by a subgingival dysbiotic microbiota. Multiple studies have determined the higher prevalence of tooth loss and poor oral hygiene in patients with Alzheimer’s disease (AD). However, the periodontal diagnosis, periodontal bacteria or mediators has not been measured to date. Aim: To determine the periodontal status, the pro-inflammatory mediators, Porphyromonas gingivalis load, and Apoliporpotein E (ApoE) in patients with AD. A complete dental examination was performed on 30 patients, and cognitive status was determined by the Montreal Cognitive Assessment (MoCA). Subgingival microbiota and GCF samples were then taken from all patients from the deepest sites. Total DNA was isolated from the microbiota samples for the quantification of the 16S ribosomal subunit. Pro-inflammatory mediators and ApoE were quantified from the gingival crevicular fluid (GCF). Patients with AD had periodontitis stage III-IV in 80%, a higher concentration of pro-inflammatory and ApoE mediators, and a higher P. gingivalis load compared to healthy subjects. The pro-inflammatory mediators, P. gingivalis load had a negative correlation with the MoCA test scores. Finally, a ROC curve was performed to assess the specificity and sensitivity of ApoE levels, detecting an area of 84.9%. In AD patients, we found a more severe periodontitis, a higher levels of pro-inflammatory mediators, and higher bacterial load. In addition, there is an increase in ApoE that allows to clearly determine patients with health, periodontitis and periodontitis and AD.